Appraisal Analysis of the Attitudinal Perspective in Texts Written by the Indonesian Migrants in Hong Kong for their Mothers - Nurdiyani, Netty; Djatmika, Djatmika; Sumarlam, Sumarlam; Wiratno, Tri; Santosa, Riyadi (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
The purpose of this research is to describe the language used by Indonesian Migrants in Hong Kong (BMI HK) as contained in the Iqro and CahayaQu Magazines which were published in 2014. The collected data were, therefore, written data. Specifically, the research tried to identify the language used by the BMI HK to their mothers. The research focused on the attitudinal perspective which comprised one of the categories of the appraisal system. The identification included three attitudinal aspects, namely affect, judgment, and appreciation. The collected data consisted of written works made by the BMI HK as they were published in the rubrics of Surat Pembaca (Readers’ Letters), Curahan Hati (Sharing One’s feelings), Berbagi Hikmah (Sharing Wisdom), and Konsultasi Keluarga (Family Consultation). From those rubrics, five pieces of writing written by the BMI HK relating to their parents/ mothers were encountered. The research showed that the negative attitudinal lexis was outnumbered than the positive attitudinal one. Of the 164 data, 27.4% were positive attitudinal and 72.6% were negative attitudinal. When the data were calculated in detail, the percentage of affect was 46.4%, judgment 32.4%, and appreciation 21.3%. The presence of the higher negative data showed that there were problems faced by the writers (the BMI HK) and their parents.